Analysis of SOR Framework Concerning Online Shopping Value and Web Satisfaction on E-Commerce - Tika Sartika; Muhammad Fikry Aransyah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Online shopping transactions on e-commerce in Indonesia are increasing. E-commerce players continue to attempt and develop strategies to attract users in shopping online. This research analyze through the SOR (Stimulus, Organism, Response) framework on the driving factors for e-commerce users, especially Shopee in making online purchases regarding online shopping value and web satisfaction provided on Shopee services, problems related to the high number of e-commerce shopping. and the amount of impulsive spending money in the large number from big sale programs that are displayed. The approach of this research was qualitative through descriptive analysis of the results of questionnaires obtained by 385 respondents in Indonesia using the Guttman Scale and interviewing 10 informants as supporting empirical data. The results of this study was reproducibility coefficient is 0.94 and a scalability coefficient is 0.63, with reliable test using the Richard Kuderson formula (KR20) is 0.2 which was declared valid and reliable. In addition, the most important driving factor for purchase intention was obtained from this study, namely the free shipping feature with a percentage of 48.1%. Recommendations for future research is to focus on research on the peak moments of online shopping, such as the Ramadan big sale, and the celebration of the national shopping day and others. In addition, expanding respondents and informants, in order to expand the study and re-design related to the framework used.